Super-resolution Imaging Realization of Costas Signal - Wang Liang; Shang Chao-xuan; He Qiang; Han Zhuang-zhi; Wang Yong-lei (Institute of Advanced Engineering and Science, 2014)
Although the ambiguity function of Costas-coded FH (Frequency Hopping) signal has a thumbtack nature, its resolution in range and velocity domain is constraint by the bandwidth and time duration also. If one target is much stronger than the others in multi-targets detection environment, the sidelobes pedestal will make possible masking via the traditional stretch signal processing. Based on the diffraction model of radar target, sparse decomposition and compressed sensing are applied to reconstruct the radar range-velocity profiles with super-resolution. In order to get the super-resolution profiles, a sparse dictionary is constructed based on the Costas echo model, different sparsity measure functions are studied, and the penalizing function method and the Lagrangian multipliers method are introduced to get the optimal result. Some schemes are introduced to get the optimal atom and the differences between these schemes are compared via simulations. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3904